일본잎갈나무 체세포배 유래 식물체의 초기 신초와 뿌리 길이, 순화용 기질이 생존율에 미치는 영향 - 이나념; Na Nyum Lee; 윤아영; A Young Yun; 김지아; Ji Ah Kim; 김태동; Tae Dong Kim; 김용욱; Yong Wook Kim; 한심희; Sim Hee Han (한국산림과학회지, 2020)
본 연구는 체세포배 발아 식물체의 세포 라인별, 순화용 기질별 생육 특성을 분석하여, 일본잎갈나무 조직 배양묘의 순화 중 생존율을 높이려는 방안을 마련하고자 실시하였다. 체세포배 발아 식물체는 라인 L14-66, L16-18, L17-B4를 사용하였으며, 순화용 기질은 낙엽송 전용 상토, 원예용 상토, 엘리포트, 피트플러그를 사용하였다. 평균 초기 신초와 뿌리 길이는 L14-66 라인이 가장 짧았고, L17-B4 라인이 가장 길었다. 세포 라인별 평균 생존율은 L17-B4 라인이 87.0%로 가장 높았고, L14-66 라인이 64.3%로 가장 낮았다. 순화용 기질별 생존율은 엘리포트와 피트플러그에서 각각 88.5%, 88.9%로 가장 높았다. L14-66 라인의 초기 신초 길이는 낙엽송 전용 상토(r = 0.852), 원예용 상토(r = 0.692), 엘리포트(r = 0.867)에서 생존율과 상관이 높았으나, 전 질소 함량이 높은 피트플러그에서는 상관이 없었다. L17-B4 라인의 초기 신초 이는 모든 순화용 기질에서 생존율과 상관이 없었다. L14-66 라인의 초기 뿌리 길이는 낙엽송 전용 상토(r = 0.986), 엘리포트(r = 0.846), 피트플러그(r = 0.802)에서 생존율과 상관이 높았으며, 유식물체의 생존율은 초기 뿌리 길이가 길수록 높았다. L17-B4 라인의 초기 뿌리 길이는 낙엽송 전용 상토(r = 0.896)와 엘리포트(r = 0.696)에서만 생존율과 상관을 보였다. 결론적으로, 유식물체의 생존율을 높이기 위해서 신초 길이보다 뿌리 길이를 우선 고려해야 하며, 피트플러그와 같이 기질 내 질소 함량이 높은 재료를 사용하거나 순화 과정 중에 질소 시비를 높여 주는 것이 좋다. 또한, 생존율을 높이기 위해 초기 생장이 빠른 라인 개발도 함께 이루어져야 한다. We analyzed the growth characteristics of each cell line and acclimating substrate of Larix kaempferi plantlets regenerated from somatic embryos, with the goal of increasing the survival rate during the acclimation phase. Somatic embryos from three embryogenic cell lines (L14-66, L16-18, and L17-B4) were used, and the acclimating substrates were commercial soils for Larix species (Larix-Soil) and horticultural corps (Hort-Soil), Elle-pot, and Peat-plug. The average initial shoot and root length was shortest in L14-66 and longest in L17-B4. The average survival rate by cell line was highest (87.0%) in L17-B4 and lowest (64.3%) for L14-66. Survival rates by substrate were highest in Elle-pot (88.5%) and Peat-plug (88.9%). The initial shoot length of the L14-66 plantlets was highly correlated with survival rates in the Larix-Soil (r = 0.852), Hort-Soil (r = 0.692), and Elle-pot (r = 0.867) substrates, but not in Peat-plug with high total nitrogen content. The initial shoot length of the L17-B4 plantlets was not correlated with the survival rate in any of the substrates. The initial root length of the L14-66 plantlets was highly related to survival rates in the Larix-Soil (r = 0.986), Elle-pot (r = 0.846), and Peat-plug (r = 0.802) substrates, and the survival rate of the plantlets was higher as the initial root length was longer. The initial root length of the L17-B4 plantlets was related to survival rate only in the Larix-Soil (r = 0.896) and Elle-pot (r = 0.696) substrates. In conclusion, to increase the survival rate of plantlets, root length should be considered over shoot length, and it is recommended to use substrates with high nitrogen content, such as Peat-plug, or to add fertilizer, during the acclimating process. In addition, in order to increase the survival rate, lines with high initial growth should be developed.